2017
DOI: 10.1242/bio.028795
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and turnover of neurofilaments in growing axonal neurites

Abstract: Neurofilaments (NFs) are thought to provide stability to the axon. We examined NF dynamics within axonal neurites of NB2a/d1 neuroblastoma by transient transfection with green fluorescent protein-tagged NF-heavy (GFP-H) under the control of a tetracycline-inducible promoter. Immunofluorescent and biochemical analyses demonstrated that GFP-H expressed early during neurite outgrowth associated with a population of centrally-situated, highly-phosphorylated crosslinked NFs along the length of axonal neurites (‘bun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 86 publications
1
18
1
Order By: Relevance
“…They are distinguished from small bundles of NFs that normally occur in neurons. They also differ from the NF bundles described by others that are enriched in phosphorylated NFH and immunoreactive with monoclonal antibody RT97 (43,44) in being hypophosphorylated (7).…”
Section: Loss Of Sacsin Leads To Bundling Of Nfs Composed Of Multiplecontrasting
confidence: 87%
“…They are distinguished from small bundles of NFs that normally occur in neurons. They also differ from the NF bundles described by others that are enriched in phosphorylated NFH and immunoreactive with monoclonal antibody RT97 (43,44) in being hypophosphorylated (7).…”
Section: Loss Of Sacsin Leads To Bundling Of Nfs Composed Of Multiplecontrasting
confidence: 87%
“…The majority of hippocampal neurons express some NFs (NF‐L, ‐M, and ‐I/INA) by DIV3, but expression patterns are heterogeneous. Interestingly, IFs are enriched in the distal regions of very early (DIV 1) growing neurites in cultured neurons, suggesting possible roles of IFs in axon growth and growth cone responses (Figure ) (Bott et al, ; Boumil, Vohnoutka, Lee, Pant, & Shea, ; Okabe, Miyasaka, & Hirokawa, ; Uchida & Brown, ; Yan, Yang, Bian, & Jing, ). What then is the evidence for IF roles in neurodevelopment, including axon growth?…”
Section: Ifs In Neuronsmentioning
confidence: 99%
“…It was initially shown that early axons are mainly composed of microtubules with only low levels of NF-M and NF-L before axons reach their synaptic targets (Perrot et al, 2008). Recent work showed that cortical neurons express VIM and nestin at 24 hr in culture, but expression of these IF subtypes is transient, but some adult neurons continue to express VIM and nestin (Bott et al, 2019a;Guo et al, 2014;Hendrickson et al, 2011;Su et al, 2013;Zhu et al, 2011) (Figure 3) (Bott et al, 2019a;Boumil, Vohnoutka, Lee, Pant, & Shea, 2018;Okabe, Miyasaka, & Hirokawa, 1993;Uchida & Brown, 2004;Yan, Yang, Bian, & Jing, 2001). What then is the evidence for IF roles in neurodevelopment, including axon growth?…”
Section: Ifs In Developing Neurons Are Structurally and Functionallmentioning
confidence: 99%
“…The early stages of neuritogenesis rely on transient expression of vimentin followed by alpha‐internexin (Boyne, Fischer, & Shea, ; Shea & Beermann, ; Shea, Paskevich, & Beermann, ; Yabe et al, ). Continued axonal maturation is accompanied by the appearance of neurofilaments (NFs), which are the major intermediate filament of mature neurons (Boumil, Vohnoutka, Lee, & Shea, ; de Waegh, Lee, & Brady, ; Lee & Shea, ; Shea & Beermann, ; Shea & Lee, ; Yuan, Rao, Veeranna, & Nixon, ). Unlike vimentin, which is downregulated during progressive neuritic outgrowth and maturation (Yabe et al, ), alpha‐internexin remains functionally associated with NFs (Yuan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive phosphorylation induces cation‐dependent NF‐NF associations that compete with transport and induce formation of NF bundles (Boumil, Vohnoutka, Lee, Pant, & Shea, ; Kushkuley et al, ; Lee, Sunil, & Shea, ; Shea & Lee, ; Sunil, Lee, & Shea, ; Yabe, Chan, Chylinski, Pimenta, & Shea, ). Bundles are likely to provide support to developing and mature axonal neurites (Boumil et al, ; Lee et al, ; Yuan et al, ). NFs are present within the first few days of neuritogenesis and are thought to provide progressive proximal‐distal support during axonal pathfinding (Lee & Shea, ).…”
Section: Introductionmentioning
confidence: 99%